The Power of Images in Paul - Collins, Raymond F., 1935- (Book collections on Project MUSE., 2008)
In his letters to the early Christian communities, the apostle Paul left for Christians of all time an array of powerful images: from the pain of a thorn in the flesh to the tenderness of a nursing mother for her children, from the competition on an athletic field to the growth of an agricultural field. In The Power of Images in Paul, Raymond Collins explores how Paul uses the ordinary to describe what is extraordinary, how Paul uses a wide range of metaphors as a means of both persuasion and clarification. But this book is more than an analysis of Paul's images themselves. Collins also examines how Paul deliberately draws from secular as well as religious and biblical themes in order to draw a culturally diverse audience into relationship with Christ. --From publisher's description.